Emergence of Escherichia coli producing extended-spectrum AmpC β-lactamases (ESAC) in animals - Haenni, Marisa; Châtre, Pierre; MADEC, Jean-Yves (Frontiers in Microbiology, 2014)
In both humans and animals, the spread of Extended-Spectrum -Lactamases (ESBL)/AmpC producers has become a major issue, particularly due to the plasmidic dissemination of most of these genes. Besides, over-expression of the chromosomal ampC gene was largely reported in human and animal Enterobacteriaceae and, more recently, modifications within the coding region of the ampC gene (encoding Extended-spectrum AmpC -lactamases (ESACs)) were shown to be responsible for an hydrolysis spectrum expanded to oxyiminocephalosporins in humans. In this study, among 6765 cattle E. coli isolates, 28 (0.37%) isolates harboring a reduced susceptibility to cefepime (MICs ranging from 0.5 to 12 g/ml) were investigated as presumptive ESACs producers. Highly conserved mutations in the promoter/attenuator region were identified at positions -88, -82, -42, -18, -1 and +58. Using sequencing and cloning experiments, amino acid substitutions of the AmpC beta-lactamase were characterized at positions 287 (mostly S287N, but also S287C), 292 (A292V) and 296 (H296P), similarly to data reported in humans. Interestingly, those cattle ESAC-producing E. coli isolates predominantly belonged to the Clonal Complex (CC)23, thus mirroring what has been described in humans. The driving forces for the selection of ESACs in animals are unknown, and their prevalence needs to be further investigated in the different animal sectors. Considering the over-representation of ESAC-producing E. coli belonging to CC23 in both humans and animals, exchanges of ESAC producers between the two populations may have occurred as well. To our best knowledge, this study is the first report of ESACs in animals worldwide, which should be considered an emerging mechanism contributing to the resistance to extended-spectrum cephalosporins in the animal population.